2009
DOI: 10.1371/journal.ppat.1000349
|View full text |Cite
|
Sign up to set email alerts
|

Severe Plasmodium falciparum Malaria Is Associated with Circulating Ultra-Large von Willebrand Multimers and ADAMTS13 Inhibition

Abstract: Plasmodium falciparum infection results in adhesion of infected erythrocytes to blood vessel endothelium, and acute endothelial cell activation, together with sequestration of platelets and leucocytes. We have previously shown that patients with severe infection or fulminant cerebral malaria have significantly increased circulatory levels of the adhesive glycoprotein von Willebrand factor (VWF) and its propeptide, both of which are indices of endothelial cell activation. In this prospective study of patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
105
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 40 publications
9
105
2
Order By: Relevance
“…However, several studies have reported that plasma ADAMTS13 antigen and activity levels are significantly reduced in CM. 26,32,33 Interestingly, only modest reductions in ADAMTS13 have been observed, with plasma levels generally remaining .30% normal values. 26,32,33 Previous in vitro studies suggest that these ADAMTS13 levels should be adequate to maintain normal plasma VWF multimer distribution.…”
Section: Adamts13 In Malariamentioning
confidence: 99%
See 3 more Smart Citations
“…However, several studies have reported that plasma ADAMTS13 antigen and activity levels are significantly reduced in CM. 26,32,33 Interestingly, only modest reductions in ADAMTS13 have been observed, with plasma levels generally remaining .30% normal values. 26,32,33 Previous in vitro studies suggest that these ADAMTS13 levels should be adequate to maintain normal plasma VWF multimer distribution.…”
Section: Adamts13 In Malariamentioning
confidence: 99%
“…26,32,33 Interestingly, only modest reductions in ADAMTS13 have been observed, with plasma levels generally remaining .30% normal values. 26,32,33 Previous in vitro studies suggest that these ADAMTS13 levels should be adequate to maintain normal plasma VWF multimer distribution. 61 Consequently, the significance of this modest reduction in plasma ADAMTS13 with respect to the accumulation of UL-VWF multimers in children with severe P falciparum malaria remains unclear.…”
Section: Adamts13 In Malariamentioning
confidence: 99%
See 2 more Smart Citations
“…Further evidence suggests ADAMTS13 deficiency in patients with systemic inflammation and severe sepsis (9,(23)(24)(25). This deficiency is associated with an increase in ulVWF and is postulated to cause TMA in patients (9,23,26).…”
mentioning
confidence: 99%